High preoperative serum leptin level is an independent risk factor for deep vein thrombosis after total knee arthroplasty in osteoarthritis patients: A prospective and cross-sectional study. Issue 21 (May 2018) - Lu, Wanli; Zhou, Sheng; Xue, Long; Dai, Bingyang; Qiao, Liang; Chen, Dongyang; Xu, Zhihong; Yao, Yao; Teng, Huajian; Jiang, Qing
Abstract : Abstract: It suggests that a high leptin level may increase the risk of venous thromboembolism (VTE) in animal studies. However, clinical studies in this field are still largely unexplored. Our objective was to evaluate the relationship between the preoperative serum leptin levels and postoperative VTE incidence in osteoarthritis (OA) patients who underwent total knee arthroplasty (TKA) at our institute. We conducted a prospective and cross-sectional study in these OA patients from March 2014 to March 2016. Preoperative leptin levels were analyzed by Luminex assays. VTE was assessed preoperatively and on postoperative day 5 and 7. The potential risk factors for VTE were also documented. We enrolled 203 OA patients. No PE was detected and DVT was diagnosed in 34 patients postoperatively. There were significant differences between the median leptin levels in DVT group and non-DVT group [25.13 ng/mL (interquartile range, 14.51–44.31) vs 18.71 ng/mL (8.26–28.99), P  = .007]. The relative risk of DVT significantly increased with natural logarithm (ln) leptin (per SD increase) (OR 2.37, 95% confidence interval (95% CI), 1.29–4.33, P  = .005). Multivariate analyses adjusted for potential confounders showed ln leptin (per SD increase) was significantly associated with the relative risk of DVT (OR 2.17, 95% CI, 1.01–4.64, P  = .046). When patients were subdivided into tertiles according to their leptin values, the OR for DVT increased with increasing tertiles of serum leptin (OR 1.03, 95% CI, 1.01–1.06, P for trend = .023). In the present study, our results indicate that a high preoperative leptin level may be an independent risk factor for postoperative DVT.